Singlet and Triplet Contributions to the Excited-State Activities of Dihydrophenazine, Phenoxazine, and Phenothiazine Organocatalysts Used in Atom Transfer Radical Polymerization - Bhattacherjee, Aditi; Sneha, Mahima; Lewis-Borrell, Luke; Amoruso, Giordano; Oliver, Thomas A A; Tyler, Jasper; Clark, Ian P; Orr-Ewing, Andrew J (Journal of the American Chemical Society, 2021)
The photochemical dynamics of three classes of organic photoredox catalysts employed in organocatalyzed atom-transfer radical polymerization (O-ATRP) are studied using time-resolved optical transient absorption and fluorescence spectroscopy. The nine catalysts selected for study are examples of N-aryl and core-substituted dihydrophenazine, phenoxazine and phenothiazine compounds with varying propensities for control of polymerization outcomes. Excited singlet-state lifetimes extracted from the spectroscopic measurements are reported in , -dimethylformamide (DMF), dichloromethane (DCM), and toluene. Ultrafast (<200 fs to 3 ps) electronic relaxation of the photocatalysts after photoexcitation at near-UV wavelengths (318-390 nm) populates the first singlet excited state (S ). The S -state lifetimes range from 130 ps to 40 ns with a considerable dependence on the photocatalyst structure and the solvent. The competition between ground electronic state recovery and intersystem crossing controls triplet state populations and is a minor pathway in the dihydrophenazine derivatives but is of greater importance for phenoxazine and phenothiazine catalysts. A comparison of our results with previously reported O-ATRP performances of the various photoredox catalysts shows that high triplet-state quantum yields are not a prerequisite for controlling polymer dispersity. For example, the photocatalyst 5,10-bis(4-cyanophenyl)-5,10-dihydrophenazine, shown previously to exert good polymerization control, possesses the shortest S -state lifetime (135 ps in DMF and 180 ps in , -dimethylacetamide) among the nine examples reported here and a negligible triplet-state quantum yield. The results call for a re-evaluation of the excited-state properties of most significance in governing the photocatalytic behavior of organic photoredox catalysts in O-ATRP reactions.